CONDITIONS, ORGANIZATION AND SOCIO-PROFESSIONAL RELATIONSOF WORK IN THE HEALTH AND WELL-BEING OF EMPLOYEES: ABIBLIOGRAPHIC REVIEW (REMUNOM, 2025)
This study analyzed the conditions, organization, and socio-professional relationships ofwork and their impacts on the health and well-being of public servants, with anemphasis on the context of the Judiciary. A literature review was conducted in theSciELO and CAPES databases. The combinations of terms used to search for articleswere: illness and professional environment and psychological well-being andmanagement or prevention. In total, 13 studies were selected, including 4 dissertations.The results indicate that task overload, lack of institutional recognition, moralharassment, and hierarchical rigidity are the main elements associated with commonmental disorders, anxiety, depression, and burnout syndrome. It was evident thattechnological advancement and teleworking, while promoting flexibility, intensifysocial isolation and weaken professional bonds. It is concluded that promoting mentalhealth in the public service requires integrated and permanent institutional policiesfocused on prevention, support, and appreciation of public servants. Among theobserved gaps, the scarcity of longitudinal empirical studies and the absence ofintersectional analyses that consider gender, race, and specific working conditions standout. It is recommended that future research explore the impact of mental health policiesand humanized management practices on the well-being and quality of life of publicservants